Konsentrasi Gas NH3 di Daerah Perkotaan: NH3 Gas Concentration in Urban Areas - DYAH ARIES TANTI; ARIF RACHMAN; OPIK TAOPIK; ASRI INDRAWATI; WIWIEK SETYAWATI; AMALIA NURLATIFAH (Jurnal Teknologi Lingkungan, 2023)
ABSTRACT The presence of ammonia gas as a pollutant in the atmosphere can cause various air pollution problems, including as a precursor to the formation of PM2,5 particulate matter which is harmful to human health. In urban areas, NH3 gas emissions come from transportation and household activities. This research was conducted to determine the concentration of ammonia gas in ambient air in urban areas using a passive sampler. Sampling locations include areas that include the center of Bandung city, namely Pasteur, Kopo, and Kebon Kalapa. Sampling was carried out from 2014–2018 with a sampling duration of one month. Based on the results of laboratory analysis, it was found that the highest concentration of ammonia gas was in the Kebon Kalapa area with the highest concentration value of 45.03 µg/m3, followed by the Kopo area of 26.88 µg/m3 and Cipedes of 11.7 µg/m3. If based on seasonal patterns, it is found that in the dry months, the concentration of ammonia gas in ambient air tends to be higher than in the wet season for the three study locations.   ABSTRAK Keberadaan gas amonia sebagai polutan di atmosfer dapat menimbulkan berbagai masalah pencemaran udara diantaranya sebagai prekursor dari pembentukan partikulat PM2,5 yang berbahaya bagi kesehatan manusia. Di daerah perkotaan emisi gas NH3 berasal dari transportasi serta kegiatan rumah tangga. Penelitian ini dilakukan untuk menentukan konsentrasi gas amonia di udara ambien daerah perkotaan dengan menggunakan metode passive sampler. Lokasi sampling meliputi daerah yang termasuk pusat kota Bandung, yaitu Pasteur, Kopo dan Kebon Kalapa. Sampling dilakukan dari tahun 2014–2018 dengan durasi sampling satu bulan. Berdasarkan hasil analisa laboratorium, diperoleh bahwa konsentrasi gas amonia tertinggi ada di daerah Kebon Kalapa dengan nilai konsentrasi tertinggi sebesar 45,03 µg/m3, selanjutnya daerah Kopo sebesar 26,88 µg/m3 dan Cipedes sebesar 11,7 µg/m3. Jika berdasarkan pola musiman diperoleh bahwa pada bulan kering kecederungan konsentrasi gas amonia di udara ambien lebih tinggi dibandingkan dengan musim basah untuk ketiga lokasi penelitian.